PENERAPAN MODEL TIME TOKEN UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA PADA MATA PELAJARAN AKIDAH AKHLAK - Kurniati, Maya; Anwar, Syaiful; Fitriani, Fitriani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Learning Akidah Akhlak (Islamic Morals and Creed) requires a teaching model that encourages active student participation. A monotonous, teacher-centered model often makes students passive and less confident in class, thus a more interactive model is needed to foster students’ self-confidence. This study aims to improve the self-confidence of XI IPA 1 students through the application of the Time Token learning model. This model was chosen because it is believed to help students become more courageous in speaking and active in classroom participation. The study employed a classroom action research (CAR) method conducted in two cycles, involving 33 students of MAN 1 Pesawaran (19 female and 14 male). The instruments used included observations of teacher and student activities as well as self-confidence questionnaires administered at the end of each cycle. The success indicator of the study was set at a minimum of 75%. The findings show a significant increase in self-confidence from the pre-cycle to cycle II. Observation results indicated an average of 31.99% in the pre-cycle, 51.22% in cycle I, and 80.37% in cycle II. Questionnaire data also showed improvement, with averages of 22.75% in the pre-cycle, 50.30% in cycle I, and 87.88% in cycle II. In conclusion, the Time Token model can effectively enhance students’ self-confidence in Islamic Education (PAI) lessons, thereby achieving the research objectives. ABSTRAK Pembelajaran Akidah Akhlak memerlukan model pembelajaran yang mendorong partisipasi aktif siswa. Model yang monoton dan berpusat pada guru membuat siswa pasif dan kurang percaya diri di kelas, sehingga dibutuhkan model pembelajaran yang lebih interaktif untuk menumbuhkan kepercayaan diri siswa. Penelitian ini bertujuan meningkatkan kepercayaan diri siswa kelas XI IPA 1 melalui penerapan model pembelajaran Time Token. Model ini dipilih karena diyakini dapat memfasilitasi siswa untuk lebih berani berbicara dan aktif dalam kelas. Penelitian menggunakan metode tindakan kelas (PTK) dengan dua siklus, melibatkan 33 siswa MAN 1 Pesawaran (19 perempuan dan 14 laki-laki). Instrumen yang digunakan meliputi observasi aktivitas guru dan siswa serta angket kepercayaan diri yang diberikan pada setiap siklus. Indikator keberhasilan penelitian adalah minimum 75%. Penelitian menunjukkan peningkatan signifikan dalam kepercayaan diri dari Pra siklus hingga siklus II. Hasil yang diperoleh dari lembar observasi menunjukkan rata-rata 31,99% pada pra-siklus, 51,22% pada siklus I, dan meningkat menjadi 80,37% pada siklus II. Data dari angket menunjukkan peningkatan, dengan rata-rata 22,75% pada pra-siklus, 50,30% pada siklus I, dan 87,885% pada siklus II. Kesimpulannya, model Time Token dapat meningkatkan kepercayaan diri siswa dalam pelajaran PAI, sehingga tujuan penelitian telah tercapai.